Usulan Perbaikan Proses Produksi Berbasis Lean Manufacturing untuk Meningkatkan Process Cycle Efficiency pada Industri Komponen Otomotif - Hana Anggraini; Tiaradia Ihsan (Fakultas Teknik Universitas Tulang Bawang, 2026)
PT XYZ faces a significant issue with the high rate of finished goods delivery delays, particularly in the Metal Line, where delays peaked at 74 occurrences in a single month. This study aims to identify the root causes of delivery delays, classify waste activities, and develop improvement proposals based on Lean Manufacturing principles. The research methods include direct observation, interviews, and data analysis using Value Stream Mapping (VSM), Process Activity Mapping (PAM), and Root Cause Analysis (RCA) with a Fishbone Diagram. Process Cycle Efficiency (PCE) is used to measure process efficiency by comparing value-added time to the total lead time required for the process. The results indicate that only 8.6% of activities are value-added, while the remaining activities are non-value-added, including waiting time, material movement, and machine setup. The proposed improvements include layout optimization, implementation of the Single-Minute Exchange of Dies (SMED) method, and the development of a future state mapping. The implementation of these improvements increased the PCE value to 10.91%, reflecting a 2.31% improvement in process efficiency and a reduction in waste activities. Therefore, the proposed improvements are expected to significantly reduce delivery delays and enhance overall production performance. Keywords: Delivery Delay, Lean Manufacturing, Process Cycle Efficiency, Value Stream Mapping, Waste